Potentially functional genetic variants in KDR gene as prognostic markers in patients with resected colorectal cancer - Dong, Guanglong (Cancer Sci, 2012)
Angiogenesis plays a key role in the development and treatment response of various tumors. The signaling transductions mediated by the binding of vascular endothelial growth factor (VEGF) to its receptor KDR (kinase insert domain receptor) is the most important pathway in tumor angiogenesis. Single nucleotide polymorphisms (SNPs) in VEGF have been extensively implicated in the etiology and treatment outcome of colorectal cancer (CRC). However, no study has been reported evaluating the role of KDR SNPs in CRC prognosis. We herein assessed the association between four potentially functional KDR SNPs and tumor recurrence in a Chinese population with 408 surgically resected CRC patients. The most significant SNP was for rs10013228 located in the KDR gene promoter. Compared with the homozygous wild‐type genotype, the variant‐containing genotypes of this SNP were significantly associated with a reduced recurrence risk with a hazard ratio (HR) of 0.53 (95% confidence interval [CI] 0.30–0.95, P = 0.032). Moreover, a borderline significant association was noted for another promoter SNP, rs2071559, with an HR of 0.67 (95% CI 0.42–1.07, P = 0.092). In stratified analysis, the associations of both SNPs were more prominent in patients receiving chemotherapy (HR = 0.47, 95% CI 0.23–0.94, P = 0.033 for rs10013228 and HR = 0.55, 95% CI 0.32–0.95, P = 0.032 for rs2071559). Further analysis revealed a protective effect on patient recurrence by chemotherapy (HR = 0.56, 95% CI 0.32–1.01, P = 0.046), which was more evident in patients with the variant‐containing genotypes of each of the two SNPs (HR = 0.09, 95% CI 0.02–0.55, P = 0.009 for rs10013228 and HR = 0.39, 95% CI 0.18–0.86, P = 0.020 for rs2071559). Collectively, our findings suggest SNPs in the KDR gene modulate CRC recurrence, especially in those receiving chemotherapy. (Cancer Sci 2012; 103: 561–568)